P2-S2.12 Condom use within intimate partnerships of female sex workers in Southern India. (10th July 2011) - Deering, K; Bhattacharjee, P; Washington, R; Bradley, J; Boily, M C; Shaw, S; Shannon, K; Ramesh, B M; Rajaram, S; Moses, S; Alary, M
Abstract : Background: Although female sex workers (FSWs) report high levels of condom use with commercial sex clients, particularly after targeted HIV preventive interventions have been implemented, condom use is often low with intimate partners. There is limited understanding regarding the factors that influence condom use with FSWs' non-commercial intimate partners, and how programs can be designed to increase condom use. The main objectives of this study were therefore to describe FSWs' self-reported intimate partners, along with interpersonal factors characterising their intimate partnerships, and to examine factors associated with inconsistent condom use within intimate partnerships. Methods: This study used data collected from cross-sectional questionnaires administered to 988 FSWs in four districts in Karnataka state in 2006. We used bivariate and multivariable logistic regression analysis to examine the relationship between inconsistent condom use (ie, "never", "sometimes" or "frequently", compared to "always") with intimate partners of FSWs (including husbands/cohabiting partners and other non-paying partners) and interpersonal factors describing these partnerships. Weighting and survey methods were used to account for the cluster sampling design. Results: Overall, 511 (51.8%) FSWs reported having husbands/cohabiting partners and 273 (26.0%) reported having other non-paying partners. Inconsistent condom use with these partners was high (77.4% and 60.4% respectively). In multivariable analysis, adjusting for social and environmental factors, the odds of inconsistent condom use with husbands/cohabiting partners and other non-paying partners were 12% (adjusted OR [AOR]: 1.12, 95% CIs 1.06 to 1.17) and 35% (AOR: 1.35, 95% CI 1.13 to 1.62) higher for a one-year increase in the duration of the relationship, respectively. The odds of inconsistent condom use with husbands/cohabiting partners was 50% lower if these partners knew that the respondent was a sex worker (AOR: 0.50, 95% CI 0.29 to 0.86). The odds of inconsistent condom use with other non-paying partners was 68% lower if the respondent reported ever having stayed or lived with these partners (AOR: 0.32, 95% CI 0.13 to 0.79). Conclusions: Improved designs for HIV preventive programs, including partner- or couples-focused programs, should be developed to address issues related to FSWs' intimate partnerships and increase condom use.